Measurement of medium-induced acoplanarity in central Au-Au and pp collisions at √sNN = 200 GeV using direct-photon+jet and π+ jet correlations - STAR Collaboration (Physical Review C, 2026)
The STAR Collaboration reports measurements of acoplanarity using semi-inclusive distributions of charged-particle jets recoiling from direct photon and π triggers, in central Au–Au and pp collisions at √sNN = 200 GeV. Significant medium-induced acoplanarity broadening is observed for large but not small recoil jet resolution parameter, corresponding to recoil jet yield enhancement up to a factor of ≈20 for trigger-recoil azimuthal separation far from π. This phenomenology is indicative of the response of the quark-gluon plasma to excitation, but not the scattering of jets off of its quasiparticles. The measurements are not well described by current theoretical models which incorporate jet quenching. © (2026), (American Physical Society). All rights reserved.
Keywords: Component (thermodynamics); Field (mathematics); Measure (data warehouse); Noise (video); Work (physics); dept.phy